A comprehensive study of clinical features and management of ulcers of the lower limb - Mohanta, Pradip Kumar; Mallik, Chinmoy; Chatterjee, Suman Kumar (International Surgery Journal, 2019)
Background: Leg ulcers are debilitating and painful, greatly reducing patient’s quality of life. These ulcers are often difficult to treat and the successful treatment of leg ulcers depends upon the accurate diagnosis and treatment of the underlying cause. Methods: This prospective cross sectional study was conducted by Department of General Surgery at College of Medicine and JNM Hospital, Nadia. The study was conducted during the period from September 2017 to August 2019 which included 193 patients presenting with ulcers of the lower limb and admitted in surgical wards of our hospital. Results: Most of the patients were engaged in agriculture (23.8%) followed by business (22.8%) and service (14.5%). 52.03% of the patients had habit of smoking, chewing tobacco and drinking of alcohol. Most of the ulcers were diabetic (36.3%) followed by venous (22.3%) (Z=2.17; p=0). Only 4.7% and 3.1% were malignant and trophic ulcers. Peripheral neuropathy (23.3%) was the most common type of ulcer followed by venous hypertension (22.3%). At the end of study period, 180 ulcers were healed, 3 had recurrence, 5 were disease free and 5 patients died. Conclusions: Thus, the study of various cases of leg ulcers arouses lot of interest and is mind boggling as far as the treatment of these cases are concerned. With the availability of arsenal of investigation wide range of antibiotics and with ever improving dressing material, there is certainly a great improvement in treatment of chronic leg ulcers.